The Problems of Borrowed Words Usage in Modern Media. - Sirotinina, Olga; Degaltseva, Anna (Philology & Human, 2022)
The intensification of the processes of globalization and digitalization of modern life led to the fact that borrowings, as a rule, from English, are actively penetrating into many languages, including Russian. With the emergence of new realities of life, there is a need for their concise nomination, which the lexical system of the native language cannot always provide. Based on the material of modern media, the authors of this article show that borrowing is a language process that has both positive and negative consequences. Positive phenomena include the enrichment of the Russian language: the expansion of its vocabulary, morphemic repertoire, the emergence of new meanings in the borrowings entrenched in the language. A negative consequence is the clogging of the Russian language, expressed in the inappropriate use of foreign language vocabulary. Borrowed words that are most actively used in modern Russian can be grouped into the following thematic groups: "Information technology", "Economics", "Politics", "Science", "Culture", "Socio-psychological phenomena", "Fashion and beauty", "Sports", "Gastronomy". The study of the National Corpus of the Russian Language shows that in the media of the second and third decades of the XXI century, foreign language vocabulary related to information technologies most often functions, which, of course, is explained by the realities of life in the modern digital world.